KOMPLEKS REKREASI SPIRITUAL BERBASIS ALAM DI LERENG MERAPI KABUPATEN MAGELANG DENGAN PENDEKATAN ARSITEKTUR LOKAL - Donatus Edna Renaldy; Marsudi Marsudi; Boni Heru Santosa (Universitas Sebelas Maret Surakarta, 2014)
Abstract: Spiritual Recreation Complex is a building as a place for tourism / recreational emphasis on the spiritual aspect as an alternative to the conventional tourist activities. Aiming to develop one’s personality and mental health through activities carried out and the results are expected to apply learning in everyday life. As a building located in the middle of the building’s traditional society should not be too contrary to the surrounding environment. The concept of designing buildings that are planned utilizing the area locality west slope of Merapi which has the potentioal of art and culture is still very guarded. Locality which is applied in the design concepts included arts and culure, the use of loval materials around, around local building form, the potential footprint, and social. The location is contoured to the challenge in designing. Land that is contoured and applied design should be able to answer the important points of local architecture into the design approach. Departing from locality slopes of Merapi, Spiritual Recreation Complex building is manifested in the form of architecture that is able to interact with the surroundings, able to blend and create a two-way relationship between the visitors with the surrounding communities. Keywords: Spiritual Recreation, Local Architecture, Merapi Slopes, Local Wisdom